Selecting the Voltage Class for a System of External Power Supply System for the Entire Life Cycle of a Gas Field - Bogachkov, I M (IOP conference series. Earth and environmental science, 2021)
This article deals with the problem of voltage class selection taking into consideration all of the life-cycle periods of a gas field based on the data from the existing gas fields in Western Siberia. The incorrect voltage class may hinder the operation of the gas field at the final relief stage. The work aims to develop criteria and algorithms for the selection of the best voltage class for the external power supply system at gas fields taking into consideration their entire life cycle. To achieve the goal set, we dealt with the following objectives: analyzing literature on gas field development technology, analyzing the actual rated electrical load in every life cycle period of the gas fields in Western Siberia; analyzing literature on the methods of determining the voltage class for industrial facilities; analyzing the existing criteria and developing new criteria for the selection of the best voltage class taking into consideration the entire life cycle of the gas fields in Western Siberia; developing a formula for the objective function to calculate the voltage class; developing selection guidelines for the best voltage class of the power supply system of gas fields that would take a number of shifting parameters throughout their life cycles; developing a generic programmatic selection algorithm for the best voltage class, and studying the power mains of the external power supply system at the existing gas fields in Western Siberia. Our research relied on the following methods: experiment planning (complete factorial experiment) and computer programming methods.